Pharmacological treatment of psoriatic arthritis: a systematic literature review for the 2015 update of the EULAR recommendations for the management of psoriatic arthritis. Issue 3 (11th December 2015) - Ramiro, Sofia; Smolen, Josef S; Landewé, Robert; van der Heijde, Désirée; Dougados, Maxime; Emery, Paul; de Wit, Maarten; Cutolo, Maurizio; Oliver, Susan; Gossec, Laure
Abstract : Objective: To update the evidence on the efficacy and safety of pharmacological agents in psoriatic arthritis (PsA). Methods: Systematic literature review of randomised controlled trials comparing pharmacological interventions in PsA: non-steroidal anti-inflammatory drugs, glucocorticoid, synthetic disease modifying antirheumatic drugs (sDMARDs) either conventional or targeted, biologicals (bDMARDs), placebo or any combination. Main outcomes were American College of Rheumatology (ACR)20–50, Psoriasis Area Severity Index 75, radiographic progression, and withdrawals due to adverse events (AEs). Multiple studies of the same intervention were meta-analysed using random effects. Results: In total, 25 papers and 12 abstracts were included. The efficacy of tumour necrosis factor inhibitors (including the recently added golimumab and certolizumab pegol) was confirmed and 16 articles/abstracts focused on 3 drugs with new modes of action: ustekinumab (UST), secukinumab (SEC) and apremilast (APR). All were placebo-compared trials and met their primary end point, ACR20. In 2 studies with UST ACR20 was met by 50% and 44% of patients with UST 90 mg, 42% and 44% with UST 45 mg vs 23% and 20% with placebo, respectively. In two studies with SEC ACR20 ranged 54% (SEC 300 mg), 50–51% (SEC 150 mg), 29–51% (SEC 75 mg) and 15–17% (placebo). In four studies with APR, ACR20 ranged 32–43% (APR 30 mg), 29–38% (APR 20 mg) and 17–20% (placebo). For all three drugs, no more withdrawals due to AEs than placebo were seen and, in general, safety appeared satisfactory. A strategy trial, TIght COntrol of Psoriatic Arthritis (TICOPA), showed better ACR responses with treatment adaptations upon tight control compared with standard care. Conclusions: UST, SEC and APR are new drugs with efficacy demonstrated for the treatment of PsA. No major safety signals arise, but long-term studies are needed. This review informed about the European League Against Rheumatism recommendations for management of PsA.